Interleukin-1 receptor antagonist modifies the changes in vital organs induced by acute necrotizing pancreatitis in a rat experimental model - Tanaka, N; Murata, A; Uda, K; Toda, H; Kato, T; Hayashida, H; Matsuura, N; Mori, T (Critical care medicine, 1995)
Interleukin-1 (IL-1) is a mediator in some critical conditions such as septic shock and multiple organ failure. Acute pancreatitis is one of the noted causes of multiple organ failure but the mechanism by which local inflammation progresses to systemic disease is unknown. In this study, we used an IL-1 receptor antagonist (IL-1ra) to investigate whether multiple organ failure due to acute pancreatitis is mediated by IL-1, as in other causes such as severe infection, trauma, and major surgery. Prospective, randomized, controlled trial. Research laboratory of a university medical school. Specific pathogen-free male Wistar rats weighing 200 to 250 g. Necrotizing pancreatitis was induced by retrograde injection of deoxycholate solution into the biliopancreatic duct. IL-1ra was injected intravenously at a dose of 10 mg/kg 15 mins before induction of acute pancreatitis and then infused continuously at a rate of 5 mg/kg/hr for the following 24 hrs. Although treatment with recombinant human IL-1ra did not affect the degree of local pancreatic insult, it significantly reduced mortality, improved urine output as an indicator of the state of shock, and ameliorated the accumulation of neutrophils into the lung in a rat experimental pancreatitis model. We concluded that multiple organ failure in severe pancreatitis is mediated, at least in part, by IL-1 through the activation of neutrophils. Furthermore, we concluded that circulatory collapse may also be important in the mechanism of the lethal effect of pancreatitis.